Lipoprotein(a) as a Risk Factor for Recurrent Acute Myocardial Infarction and Mortality: Insights from Routine Clinical Practice - David Šuran; Vojko Kanič; Peter Kokol; Tadej Završnik; Florjan Verhnjak; Bojan Žlahtič; Andreja Sinkovič; Franjo Husam Naji (Diagnostics)
Background: Lipoprotein(a) [Lp(a)] is a well-established risk factor for incident atherosclerotic cardiovascular (CV) disease. However, evidence regarding its association with recurrent events is limited. To address this gap, we conducted a retrospective analysis of routine clinical data, focusing on patients hospitalized for acute myocardial infarction (AMI) between 2000 and 2022 with available admission Lp(a) results. Methods: Patients were stratified into three groups based on their Lp(a) level (≤50 mg/dL, 51–90 mg/dL, and >90 mg/dL). A multivariable-adjusted Cox regression analysis was performed to assess the associations of Lp(a) with recurrent AMI, CV mortality, and all-cause mortality. Results: A total of 2248 patients (31.5% women), with a mean age of 64.7 ± 12.2 years, were retrospectively followed until 31 December 2022, or death. The multivariable-adjusted hazard ratios (HRs) for recurrent AMI were 1.01 (p = 0.921) for levels 51–90 mg/dL and 1.51 (p = 0.013) for levels > 90 mg/dL, compared with levels ≤ 50 mg/dL. The corresponding HRs for CV mortality were 1.13 (p = 0.300) and 1.14 (p = 0.348), and those for all-cause mortality were 1.09 (p = 0.310) and 1.20 (p = 0.090), respectively. Stratification by sex and age revealed a significant association of Lp(a) with recurrent AMI only in women aged > 65 years, with adjusted HRs of 2.34 (p = 0.013) for levels 51–90 mg/dL and 3.94 (p < 0.001) for levels > 90 mg/dL, compared with levels ≤ 50 mg/dL. Conclusions: In the presented study, Lp(a) was associated with a significantly higher risk of recurrent AMI only in women aged > 65 years with Lp(a) levels > 50 mg/dL. We found no significant associations between Lp(a) and CV or all-cause mortality.